Effects of Amino Acid and Energy Intake During Late Gestation on Piglet Birth Weight and Reproductive Performance of Gilts and Sows Housed Under Commercial Conditions - M. A. Goncalves; K. M. Gourley; S. S. Dritz; M. D. Tokach; N. M. Bello; J. M. DeRouchey; J. C. Woodworth; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2015)
The objective of this study was to determine the effects of amino acid (AA) and energy intake during late gestation on piglet birth weight and reproductive performance of high-performing gilts and sows housed under commercial conditions. At d 90 of gestation, a total of 1,102 females (PIC 1050) were housed in pens by parity group (P1 or P2+), blocked by weight within each pen, and each female was randomly assigned to dietary treatments within weight block. Dietary treatments consisted of combinations of 2 standardized ileal digestible (SID) AA (10.7 or 20.0 g SID Lys intake/d with other AA meeting or exceeding the NRC [2012] recommendations as a ratio to Lys) and 2 energy intakes (4.50 or 6.75 Mcal/d intake of NE) in a 2 × 2 factorial arrangement. Data were analyzed using generalized linear mixed models with parity group and dietary treatments as the linear predictor and random effects of pen as the experimental unit for parity and the individual female as the experimental unit for dietary treatments. With high energy intake, the magnitude of BW gain during late gestation was greater (AA × Energy, P<0.001) with increasing AA intake compared with increasing AA at low energy intake. Gilts gained more weight at low energy intake than sows (parity × energy, P<0.001); however, there was no evidence for differences (P = 0.601) in weight gain between gilts and sows at high energy intake. Sows fed high-energy intake had marginally reduced probability of piglets born alive (parity × energy, P = 0.092) compared with sows fed low energy, but no evidence for differences in gilts was observed. This was due to the increased probability (parity × energy, P = 0.014) of stillborns to be higher in sows fed high energy intake. There was no evidence for differences between the dietary treatments for litter birth weight and individual piglet birth weight of total piglets born. However, individual born-live birth weight was heavier (P =0.011) for females fed high-energy intake treatments compared to those with low energy intake. Born-alive piglets from sows were heavier (P<0.001) than those from gilts. There was a lower probability (P = 0.034) of pre-weaning mortality for females fed high AA intake compared to low AA intake, regardless of energy level. There was no evidence for differences between the dietary treatments on farrowing rate, number of total piglets born, and percent of piglets born alive in the subsequent cycle. In conclusion, 1) body weight gain of gilts and sows depends not only on energy but also AA intake, 2) sows fed an increased amount of energy had increased stillborn rates, 3) the positive effect of increased amount of feed during late gestation on individual piglet birth weight, 30 g per pig, was due to energy rather than AA intake.
Keywords: amino acids; birth weight; energy; gilt; sow